From multimedia communication to transmedia communication: a theoretical review of current journalistic narratives - Robledo Dioses, Kelly; Atarama Rojas, Tomás; Palomino Moreno, Henry (Estudios sobre el Mensaje Periodístico, 2017)
The emergence of the different media has enriched the media ecosystem, making it in an ideal scene for the birth of new communication models which pursue the combined use of different channels for distribution of content. In this context, the transmedia storytelling was born, a model that consists in a story that is expanded through different media and is enriched with the particular characteristics of each support and the audience participation. The present paper begins with a theoretical review of the current narratives, focusing on the transmedia model, then make an analysis about the content management of the Cosas Group in Peru, in order to explore if the company aims to transmedia communication model.
Keywords: Communication; transmedia; story; content.